ZIT E-Store: Laptop Finder App - Zainal, Zarif Idzham; Ab. Aziz, Mohamad Firdaus (Applied Information Technology And Computer Science, 2022)
Brands for a computer, especially laptops, are becoming more and more numerous. This makes it a problem for consumers to make a choice. This is because, there are some users who have no knowledge about computers. Therefore, this application was developed with the aim of helping users especially those who first want to use a computer to choose the type of laptop according to their suitability. Therefore, this application is to help facilitate users to make laptop choices. Users of this application consist of two main groups, namely the company ZIT Services & Solutions as administrators and users of the application itself. Users of this application will have access to the types of laptops available at ZIT Services & Solutions. In addition, on behalf of the administrator is to update the latest information and prices for the selection of laptops. Users of this application have to answer the questions given according to the understanding of the user which is divided from beginner, intermediate and advanced. After answering the questions posed, the application will provide suggestions for the selection of laptops. This application uses a prototype methodology and uses Android Studio as the main software and Java as the programming language as well as Firebase to store the data. In conclusion, this application is able to help users to facilitate in the selection of laptops, especially users who are still new in the field of computing.